Antimicrobial resistance in fish and poultry: Public health implications for animal source food production in Nigeria, Egypt, and South Africa - Okon, Ekemini M.; Okocha, Reuben C.; Adesina, Babatunde T.; Ehigie, Judith O.; Alabi, Olayinka O.; Bolanle, Adeniran M.; Matekwe, N.; Falana, Babatunde M.; Tiamiyu, Adebisi M.; Olatoye, Isaac O.; Adedeji, Olufemi B. (Frontiers in Antibiotics, 2022)
Antimicrobial resistance (AMR) is a significant threat to global public health. Specifically, excessive usage of antimicrobials in food animal production is one significant reason for AMR development in humans. Therefore, it is essential to identify the trends of AMR in fish and poultry and develop better surveillance strategies for the future. Despite this imperative need, such information is not well documented, especially in Africa. This study used a systematic review to assess AMR trend, spatial distribution, and incidence in fish and poultry research in Nigeria, Egypt, and South Africa. Literature assessment was conducted for published studies on AMR between 1989 and 2021 using the Scopus and Web of Science databases. One hundred and seventy-three relevant articles were obtained from the database search. Egypt was the leading exponent of antimicrobial resistance research (43.35%, 75 studies), followed by Nigeria (39.31%, 68 studies), then South Africa (17.34%, 30 studies). The majority of the antimicrobial resistance studies were on poultry in Egypt (81%, 61 studies), Nigeria (87%, 59 studies), and South Africa (80%, 24 studies). Studies on fish were 17% (13 studies), 9% (6 studies), and 10% (3 studies) in Egypt, Nigeria, and South Africa, respectively. Antimicrobial resistance patterns showed multiple drug resistance and variations in resistant genes. AMR research focused on sulfamethoxazole groups, chloramphenicol, trimethoprim, tetracycline, erythromycin, and ampicillin. Most studies employed the disk diffusion method for antimicrobial susceptibility tests. Among the four mechanisms of AMR, limiting drug uptake was the most reported in this study (both in fish and poultry). The findings reveal public and environmental health threats and suggest that it would be useful to promote and advance AMR research, particularly for countries on the global hotspot for antimicrobial use.